(untitled) (Journal of Fatwa Management and Research, 2022)
Marriage in Islam is a lawful connection between a man and a woman in perpetuity. It is accomplished with the consent and full acceptance of both of them according to the proper provisions. Marriage is based on solid foundations, strong principles, and high ethics. The rights and responsibilities between the spouses are established with the Qur’an and Sunnah, in achieving the high purposes of marriage and providing everlasting stability in order to achieve the happiness that every family dream about it. On the other hand, since marriage is a serious responsibility either in marriage or divorce so not permissible to joke. Because marriage is a heavy covenant that God has taken upon the children of Adam. Therefore, all the rights and duties that entail between the spouses must be fulfilled and must hold with favours or being discharged with kindness. So, for this, we find Malaysians have taken all precautionary means and methods that guarantee stability and continuity in marriage. A Malaysian cannot apply for the marriage contract unless he/she takes a training course certificate that qualifies him/her to manage and bear family responsibility. And if it is difficult to live together, then they go to Advisory Committee, to remove the misunderstanding between the spouses, to settle their differences, and preserve the bridge of affection between them. In addition, that divorce can only take place in court. The problem of the research is the high rate of divorce in the Islamic world, so perhaps this research will contribute to the emergence of appropriate solutions to this problem, and it is known that the human being is composed of two main important elements, namely the body and the soul, and they need to be satisfied, and their emptiness is a reason for the emergence of formalities. This research aims to highlight the strengths of Malaysian family treatments to enhance them, and to benefit from their positive aspects in the rest of the Islamic world. This study will include a presentation of the pre-emptive methods and the post-remedial measures that the reconciliation committee undertakes before submitting the case to the Shariah court judge. In his study, the researcher will take this descriptive and analytical approach to find out the phenomena and then search for an accurate logical explanation and analysis suitable for them, in order to reach the required results.